Norway : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This Selected Issues paper examines the role of the State Petroleum Fund in Norwegian economic policy, as a means to promote a sustainable long-term fiscal position and to help maintain the competitiveness of the non-oil ('mainland') economy in the face of high oil export revenues. The paper documents the historical development of the wage bargaining framework in Norway, a country with a fairly centralized framework. It also compares recent wage developments in Norway with those of its trading partners to assess the implications for Norway's international competitiveness.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet